A high-order three dimensional numerical manifold method with continuous stress/strain field. (August 2020) - Yang, Yongtao; Wu, Wenan; Zheng, Hong; Liu, Xuewei
Abstract: A high-order(HO) three dimensional numerical manifold method (HO3DNMM) is proposed. In the present numerical model, HO global displacement function can be built without using extra nodal DOFs/nodes. Additionally, continuous stresses/strains among inter-element faces can be obtained with the HO3DNMM without using any stress smoothing technique. A number of numerical examples have been adopted to investigate the properties of the proposed HO3DNMM. Numerical results assessed from the HO3DNMM indicate that 1) HO3DNMM doesn't suffer from the LD (linear dependence) issue; 2) For discretized model with regular meshes, accuracy of the HO3DNMM is much better than that of the T3DNMM (traditional 3DNMM); 3) HO3DNMM is immune from the mesh distortion, which is a very attractive property as compared to the T3DNMM.